The role of prebiotics and nutrition in early stages for brain and socio-emotional development : A literature review - Ramayulis, Rita; Wasito, Erika (Indonesian Nutrition Association, 2022)
Introduction. The first 1000 days of life is the most crucial period for physical and neuro-emotional development. Since prenatal, the organ development had started and affected by many factors. Healthy neurodevelopment is dependent on socioeconomic, interpersonal and/or family, and nutritional factors. Macro- and micro-nutrients deficiencies may disrupt neurodevelopmental process. Iron, zinc, and iodium has been proven to affect brain development intrauterine and continues after birth. Prebiotics also play a role in neurodevelopmental through brain-gut-axis, but also beneficial on overall health. Methods. Advanced search for relevant literatures in PubMed, Cochrane, and Willey was conducted. After assessing the relevancy and eligibility, articles were selected and critically appraised. Conclusions. Prebiotics supplementation is beneficial in promoting gut health, thus also play a role in immune pathway and influence brain function. Many studies also shown that prebiotics might be used as additional therapy in diseases that related to gut health i.e functional gastrointestinal disorders, obesity, and allergy.